Transforming Islamic Zakat Governance Through Digital Systems and Adaptive Organizational Culture - Irfan Akadji; Nurus Sa'adah; Slamet Haryono (UAS PRESS, 2026)
This study examines the optimization of BAZNAS Gorontalo’s performance through system digitalization and adaptive organizational culture within the framework of Islamic zakat governance. Using an integrative literature review approach, this research analyzes scholarly works related to digital transformation, organizational culture, Islamic philanthropy, and zakat management institutions. Previous studies have mainly focused on technological aspects of digital zakat, while limited attention has been given to the relationship between digitalization, adaptive culture, and local socio-religious characteristics in regional zakat institutions. The findings indicate that digital transformation has the potential to improve efficiency, transparency, accountability, and service quality in zakat management. In the perspective of Islamic governance, digitalization also supports the implementation of amanah, public trust, and accountable Islamic social finance management. Among the organizational culture dimensions examined, the adhocracy culture is viewed as the most supportive of digital transformation due to its emphasis on innovation and adaptability. In addition, innovation-oriented leadership plays an important role in strengthening organizational transformation. This study contributes a conceptual framework integrating digital transformation, adaptive organizational culture, and Islamic governance values in strengthening contemporary zakat institutions and digital Islamic philanthropy.